An Observational Study between Intrathecal Fentanyl and Butorphanol with Low Dose Bupivacaine to Facilitate Early Ambulation in Perineal Surgeries - Malini Mehta; Soumya Jha; Pooja Shah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Neuraxial opioids are widely used with local anaesthetics as they allow lower dose of local anaesthetics while providing adequate anaesthesia and faster recovery from spinal anaesthesia because of their sympathetic and motor nerve sparing activities. In the last few years the number of surgeries performed on an ambulatory basis has increased worldwide because of many advantages like short hospital stay, less chance of wound infection and less chances of deep vein thrombosis.Methods: 64 patients of ASA- I or II of either gender who underwent perineal surgeries were divided into two groups of 32 each:- Group BF patients received 1ml of 0.5% hyperbaric bupivacaine with 20µg fentanyl(0.4ml) and Group BB patients received 1ml of 0.5% hyperbaric bupivacaine with 200µg butorphanol(0.2ml) and normal saline(0.2ml).Patients were observed for onset of sensory and motor blockade, duration of sensory and motor blockade, duration of analgesia and time to unassisted ambulation. There was no difference in onset of sensory and motor blockade between the two groups(P> 0.005).Patients receiving butorphanol had statistically significantly longer duration of sensory and motor blockade and duration of analgesia than fentanyl(p-0.001).Patients receiving fentanyl were observed to ambulate unassisted significantly early compared to butorphanol (p-0.001).Conclusion: Patients receiving intrathecal fentanyl 20µg can ambulate earlier compared to patients receiving butorphanol 200µg when used as an adjuvant with low dose hyperbaric bupivacaine 0.5% without any complication.